Legal Protection for Women Victims of Psychological Domestic Violence Based on Enactment Number 23 of 2004 - Ni Nyoman Muryatini (Jurnal Hukum Prasada, 2023)
According to National Commission on Violence against Women’s annual record in 2020, within a period of 12 (twelve) years, violence against women increased by 792%. It means that violence against women in Indonesia for 12 (twelve) years increased almost 8 (eight) times. Psychological violence against women in the household is an act against the law, a violation of human rights, a crime against human dignity, and a form of discrimination that must be abolished. This study aims to examine the legal protection for women victims of psychological violence in the household based on the enactment of domestic violence elimination. The method used in this research is normative legal research which makes the norm system the centre of its study with the aim of providing legal arguments as a basis for determining whether an event is right or wrong and how the event should be according to law. The results showed that the government has made efforts to protect women victims of psychological violence in the household. Preventively bypassing the constitution of domestic violence elimination and repressively by providing protection and services needed by victims in the context of recovery. Domestic violence is included in the complaint offence; therefore, the victim must report to the investigator related to the violence experienced so that legal proceedings can be carried out immediately.